EFL TEACHERS' AND PARENTS' PERCEPTIONS OF TEAMS IN ENGLISH LANGUAGE TEACHING IN TULKARM'S HIGHER PRIMARY SCHOOLS DURING THE GAZA WAR 2023-2024 - Beesan Fawaz Ahmad Khalilia (جامعة النجاح الوطنية, 2025)
This study examines the effectiveness of Microsoft Teams as a tool for English as a Foreign Language (EFL) instruction in Tulkarm during the Gaza War, which began in October 2023. The ongoing conflict disrupted traditional classroom-based education, pushing schools and universities to adopt online platforms under severe constraints. The research draws on three theoretical frameworks—Technology Acceptance Model (TAM), Constructivist Learning Theory, and Bronfenbrenner’s Ecological Systems Theory—to analyze the dynamics of digital learning in a crisis context. A mixed-methods approach was employed, combining quantitative data from a structured questionnaire distributed to 60 EFL teachers and parents, with qualitative data obtained through semi-structured interviews. Quantitative data were analyzed using SPSS standard deviations and ANOVA), while interview transcripts underwent thematic content analysis. The findings revealed a moderate perception of Microsoft Teams' effectiveness among both teachers and parents. While the platform was praised for maintaining a minimum level of instructional continuity, significant limitations were identified. These included frequent power outages, weak internet connectivity, a lack of adequate digital devices, and challenges related to students’ motivation, participation, and psychosocial well-being. The interviews highlighted disparities in digital literacy, with many parents unable to support their children effectively, and some teachers lacking sufficient training. Nonetheless, adaptive practices and emotional support helped mitigate some of the challenges. Based on these findings, the study recommends enhancing teacher training in digital pedagogy, providing technical guidance and resources for parents, and improving infrastructure in conflict-affected areas. The integration of interactive content, blended learning approaches, and trauma-informed practices is also encouraged to address both educational and emotional needs. The study emphasizes that successful digital learning in crisis zones requires a holistic strategy that accounts for the technological, pedagogical, and social dimensions of education.
تصورات معلمي اللغة الانجليزية كلغة اجنبية وأولياء الأمور حول دور برنامج التيمز في تعليم اللغة الانجليزية في المرحلة الأساسية العليا في مدارس محافظة طولكرم خلال حرب غزة 2023-2024